Til Death Do Us Part - Quick, Amanda ([Prince Frederick, MD] Jove / Berkley a Penguin Random House, 2016)
Calista Langley operates an exclusive introduction agency in Victorian London, catering to respectable ladies and gentlemen who find themselves alone in the world. Now a dangerously obsessive individual has begun sending her trinkets and gifts suitable only for those in deepest mourning: a black mirror, a funeral wreath, a ring set with black jet stone.
Keywords: Man-woman relationships -- Fiction; Stalkers -- Fiction; London (England) -- Social life and customs -- 19th century; Fiction